Selectfluor®-enabled photochemical selective C(sp)-H(sulfonyl)amidation - Chen, Yuehua; Yang, Boxuan; Li, Qian-Yu; Lin, Yu-Mei; Gong, Lei (Chemical communications (Cambridge, England), 2022)
Transition metal- and photosensitizer-free C(sp 3 )-H (sulfonyl)amidation reactions have been realized by employing Selectfluor® as a versatile reagent, functioning as a photoactive component, a HAT precursor and an oxidant. Various toluene derivatives, cycloalkanes, natural products and bioactive molecules can be converted into N -containing products under mild conditions in good yield and with high chemo- and site-selectivity. Chemo- and site-selective C(sp 3 )-H sulfonylamidation and amidation of toluene derivatives, cycloalkanes, natural products and bioactive molecules has been achieved by employing Selectfluor® as a versatile reagent.